Discovery of a pre-cataclysmic binary with unusual chromaticity of the eclipsed white dwarf by the GPX survey. Issue 4 (27th February 2020) - Krushinsky, Vadim; Benni, Paul; Burdanov, Artem; Antokhin, Igor; Antokhina, Eleonora; Jehin, Emmanuël; Barkaoui, Khalid; Fitzsimmons, Alan; Gibson, Christopher; Gillon, Michaël; Popov, Alexander; Baştürk, Özgür; et al.
ABSTRACT: We report the discovery of a relatively bright eclipsing binary system, which consists of a white dwarf (WD) and a main-sequence K7 star with clear signs of chromospheric and spot activity. The light curve of this system shows ∼0.2 mag ellipsoidal variability with a period of 0.297549 d and a short total eclipse of the WD. Based on our analysis of the spectral and photometric data, we estimated the parameters of the system. The K7V star is tidally deformed but does not fill its Roche lobe (the filling factor is about 0.86). The orbital inclination is i = 73_.^°1 ± 0_.^°2, and the mass ratio is q = M 2 / M 1 ≈ 0.88. The parameters of the K7V star are M 2 ≈ 0.64 M⊙, R 2 = 0.645 ± 0.012 R ⊙, and T 2 ≈ 4070 K. The parameters of the WD are M 1 ≈ 0.72 M⊙, R 1 = 0.013 ± 0.003 R ⊙, and T 1 = 8700 ± 1100 K. Photometric observations in different bands revealed that the maximum depth of the eclipse is in the SDSS r filter, which is unusual for a system of a WD and a late main-sequence star. We suspect that this system is a product of the evolution of a common-envelope binary star, and that the WD accretes the stellar wind from the secondary star (the so-called low-accretion-rate polar, hereafter LARP).